Picornaviral Gene Order: Comparison of a Rhinovirus with a Cardiovirus - McLean, Charles (1973)
We describe conditions for unmasking virus-specific protein synthesis in cells infected with rhinoviruses 1A and 2. The gene order and cleavage pattern of rhinovirus 1A show many similarities to those of encephalomyocarditis virus and of poliovirus.